La responsabilidad del empleador por accidentes de trabajo y enfermedades ocupacionales: retrospectiva y futuro - Puntriano Rosas, César (2021)
The recent trend in labor jurisprudence passes liability to the employer in the event of an accident at work or occupational disease. This violates the theory of contractual civil liability, applicable to the employment relationship, which requires fraud, gross negligence or at least slight negligence for the generation of the employer’s duty to compensate the employee. In this paper we legally analyze how employer responsibility has evolved and critically approach the current criteria, formulating some proposals for future change.